Characteristics of Women with Postpartum Hemorrhage who do not Respond to B-Lynch Suture and Require Hysterectomy - Fazilet Kübra Boynukalın; Ayşe İlknur ARAL (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Aim of this study is to criticize the women with postpartum hemorrhage due to uterine atony after vaginal delivery. STUDY DESIGN: This was a retrospective analysis performed in Şanlıurfa Maternity Hospital, from September 2008 to August 2010. Criteria for inclusion of the patients in the study were requirement of B-Lynch suture for intractable postpartum hemorrhage (PPH) due to uterine atony after vaginal delivery. The cases were identified by searching operating room records and patient files. There were 51 cases that B-Lynch suture was performed for intractable PPH due to uterine atony after vaginal delivery. In group 1 there were 12 cases that B-Lynch suture was failed and lead to hysterectomy and in group 2 there were 39 patients that B-Lynch suture achieved to cease the hemorrhage. RESULTS: In group 1; the mean age, gravidity and parity of women were 31±4.8, 5.2±2 and 3.8±2.2 respectively. Several high-risk antenatal obstetric to conditions were observed in 8 of 12 (66.7%) women. Induction or augmentation of labor was performed all of the patients who required hysterectomy. In group 2; the mean age, gravidity and parity of women were 26.5±5.5, 3.6±1.9 and 2.3±1.9 respectively. Induction or augmentation of labor was performed 8 of 39 women (20.1%) in group 2. CONCLUSION: Multiparity and induction or augmentation of labor seems to be the major characteristics of women who required hysterectomy after failed B-Lynch suture.